Surgical outcomes of patients with stage IA2 cervical cancer treated with radical hysterectomy - Sukanda Mahawerawat (2018)
Background: This study was undertaken to evaluate the surgical outcomes of patients with stage IA2 cervical cancer treated with radical hysterectomy. Data for 58 patients who underwent modified radical hysterectomy or radical hysterectomy with pelvic lymphadenectomy between January 2003 and December 2012 at Chiang Mai University Hospital were retrospectively reviewed. The analysis included clinico-pathological risk factors (nodal metastasis, parametrial involvement), adjuvant treatment, 5-year disease-free survival and 5-year overall survival. All pathologic slides were reviewed by a gynecologic pathologist. Follow-up methods included at least cervical cytology and colposcopy with directed biopsy if indicated. Univariate analysis was performed to identify factors associated with median survival. At the median follow up time of 73 months, the 5-year disease-free survival and the 5-year overall survival were 97.4% and 97.4%, respectively. Two (3.4%) patients had pelvic lymph node metastases. In a univariate analysis, there was no statistically significant association between survival and prognostic factors such as age, histological cell type, lymph-vascular space invasion, vaginal margin status and lymph node status. Surgical and survival outcomes of women with stage IA2 cervical cancer are excellent. No parametrial involvement was detected in our study. Patients with stage IA2 cervical cancer may be treated with simple or less radical hysterectomy with pelvic lymphadenectomy.